Da’wah and the Improvement of Islamic Higher Education Institution’s Image with Communication Strategy of Public Relations - Fathan Fathan; Ahmad Saifuddin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2019)
Image is an important component for education institutions to increase public trust. One of the efforts in improving this image is the communication strategy performed by the public relations officers in Higher Education Institutions (HEI). Islamic universities as da’wah organization also is expected to have a good image. This study is to reveal the communication strategies of two Islamic HEI: State Institute for Islamic Studies (IAIN) Surakarta), and State Institute for Islamic Studies (IAIN) Salatiga, and the improvement of their images by public relations with da'wah. These two Islamic HEI selected as the object of research because they are still in level institute, so, they have great opportunities for developing to higher level. The approach used in this research is a qualitative approach with a case study method. The data collection techniques are interviews, observation, and document analysis. The result shows that IAIN Surakarta improves its image by using communication strategies in accreditation of study programs and academic journals, as well as transformation into a university. IAIN Salatiga, meanwhile, improves its image by using strategies of green campus and international journal publication. Therefore, the public relations office considers applying the principle of da'wah to encourage people to empower. Citra merupakan komponen penting bagi perguruan tinggi dalam meningkatkan kepercayaan masyarakat. Upaya peningkatan citra ini dapat dilakukan dengan strategi komunikasi oleh bagian hubungan masyarakat (Humas) di perguruan tinggi. Perguruan tinggi Islam sebagai lembaga dakwah juga dituntut memiliki citra yang baik. Penelitian ini berupaya mengetahui strategi komunikasi dua perguruan tinggi keagamaan Islam, yaitu Institut Agama Islam Negeri Surakarta dan Institut Agama Islam Negeri Salatiga. Kedua perguruan tinggi tersebut dipilih karena masih level institut sehingga memiliki peluang berkembang ke level lebih tinggi. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan metode studi kasus. Adapun teknik pengumpulan data dilakukan dengan wawancara, pengamatan, dan analisis dokumentasi. Penelitian menemukan bahwa IAIN Surakarta berupaya melakukan strategi komunikasi untuk meningkatkan citra melalui akreditasi program studi, jurnal, dan transformasi menjadi universitas. Sedangkan IAIN Salatiga melakukan strategi komunikasi untuk meningkatkan citra melalui kampus hijau dan publikasi jurnal internasional. Dengan demikian, bagian Humas dianggap menerapkan prinsip dakwah untuk mengajak masyarakat melakukan pemberdayaan.